Effects of Glutamate Receptor Agonists on the P13 Auditory Evoked Potential and Startle Response in the Rat - Simon, Christen; Wallace-Huitt, Tiffany; Thapa, Priyenka; Skinner, Robert D.; Garcia-Rill, Edgar (Frontiers in Neurology, 2011)
The P13 potential is the rodent equivalent of the P50 potential, which is an evoked response recorded at the vertex (Vx) 50 msec following an auditory stimulus in humans. Both the P13 and P50 potentials are only present during waking and rapid eye movement (REM) sleep, and are considered to be measures of level of arousal. The source of the P13 and P50 potentials appears to be the pedunculopontine nucleus (PPN), a brainstem nucleus with indirect ascending projections to the cortex through the intralaminar thalamus (ILT), mediating arousal, and descending inhibitory projections to the caudal pontine reticular formation (CPRF), which mediates the auditory startle response (SR). We tested the hypothesis that intracranial microinjection (ICM) of glutamate (GLU) or GLU receptor agonists will increase the activity of PPN neurons, resulting in an increased P13 potential response, and decreased SR due to inhibitory projections from the PPN to the CPRF, in freely moving animals. Cannulae were inserted into the PPN to inject neuroactive agents, screws were inserted into the Vx in order to record the P13 potential, and electrodes inserted into the dorsal nuchal muscle to record electromyograms (EMGs) and SR amplitude. Our results showed that ICM of GLU into the PPN dose-dependently increased the amplitude of the P13 potential and decreased the amplitude of the SR. Similarly, ICM of NMDA or KA into the PPN increased the amplitude of the P13 potential. These findings indicate that glutamatergic input to the PPN plays a role in arousal control in vivo, and changes in glutamatergic input, or excitability of PPN neurons, could be implicated in a number of neuropsychiatric disorders with the common symptoms of hyperarousal and REM sleep dysregulation.